PROTEIN TEST WITH CHEMICAL SOLUTION IN IDENTIFYING NUTRIENT CONTENT IN FOOD MATERIAL - Wahdania; Fitria Porodjia; Srikit Nurkamiden (Journal of Health, Technology and Science (JHTS), 2021)
This study aims to find out the four factors that because proteins can be denatured, Knowing the solubility of proteins, as well as Knowing the bond of peptides in proteins, the presence of free and aromatic amino. The method used in this study is qualitative research that is descriptive, with sampling techniques that use purposive sampling method.The results showed that observations of protein denaturation that aims to see the presence of deposits in milk and the results obtained that does not occur precipitation, deposition by metals as for the results obtained that is only raw egg whites that do not occur precipitation while for the other 3 samples occur precipitation. The results of the precipitation test by alcohol obtained that tubes 1 and 2 there are no deposits while for tube 3 there are deposits, protein solubility test is obtained that the sample 1,2,4 insoluble and there are deposits while for cheese samples are only insoluble. biuret test observations obtained the occurrence of discoloration in the sample. As for the Xanthoprotein test obtained results from the sample 1,2,4 there was a change in sediment and color while for samples 3 and 5 Only changes in sediment.